Biochemical study on the constituents of apricot seed kernels - Ali Kassem, Mohammed (Al-Mukhtar Journal of Sciences, 2005)
The main Objectives of this study are: (1) Investigated that the major chemical composition of the apricot kernels to show to what such wastes might be used in edible consumptions, (2) Isolation, characterization and evaluation of its proteins. We found that apricot kernels contained higher level of protein (26.3 %). The essential amino acids comprise (34.3%) of the total amino acids, isoleucine was the most predominant one followed by valine. The chemical scores of essential amino acids and protein efficiency ratio (PER) were also determined. The Distribution of extracted protein showed a wide range of variation among the fractions, the albumins represent the highest proportion of the extracted proteins followed by globulins, prolamins and glutelins. The solubility at alkaline pH, up to 9 was higher than that recorded at neutral pH, the minimum solubilities of the proteins concentrates were between pH 4 and 5 which indicate the proximity of these pH values to the isolelectric point, where most of the amino acids could exist in the Zwitter ionic form. The other constituents are carbohydrate (13.9%), crude fiber (2.5 %), ash (3%) and crude oil (48%). Determination of minerals indicated that there are higher level of K, Ca, Na, Mg, Fe, Mn, Zn and Cu in apricot kernel samples.